STABILITY OF THE FUNCTIONAL EQUATION IN FUZZY BANACH SPACES - Pratap Mondal; Nabin Chandra Kayal; Tapas Kumar Samanta (Journal of New Theory)
Different kind of stability have been studied concerning several areas of mathematics and fuzziness of such concepts, which is an extension of the former, are being introduced in recent times. The object of the present paper is to appraise generalization of the Hyers-Ulam-Rassias stability theorem for the functional equation f ( 2 x + y ) + f ( x + 2 y ) = 4 f ( x + y ) + f ( x ) + f ( y ) in fuzzy Banach spaces .